MANAJEMEN SUPERVISI AKADEMIK DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH (PROBLEM-BASED LEARNING) DI SMK NEGERI 1 SUKALUYU - Rita Santirahayu; Nirwan Rosadi; Fitria Aprilianti; Hendri Haerudin; R Supyan Sauri (STKIP Subang, 2026)
This study aims to describe and analyze the management of academic supervision in improving the effectiveness of Problem-Based Learning (PBL) at SMK Negeri 1 Sukaluyu. The study is grounded in the importance of implementing PBL in vocational education to develop students’ critical thinking, collaboration, communication, and problem-solving skills in accordance with the needs of industry and the labor market. However, the implementation of PBL still faces several challenges, including teachers’ limited ability to design learning activities, manage instructional time, and facilitate student discussions and investigations. This research employed a qualitative approach using a descriptive-exploratory method. The research participants consisted of the principal, the vice principal for curriculum affairs, and four vocational subject teachers implementing PBL. Data were collected through in-depth interviews, passive participatory observations, and document analysis. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings indicate that academic supervision implemented systematically through planning, observation, evaluation, and follow-up stages effectively improves the implementation of PBL. Academic supervision positively impacts lesson planning quality, time management, classroom group management, and teachers’ pedagogical competence. Furthermore, student learning activities improved significantly, as reflected in increased questioning, participation in discussions, presentation skills, teamwork, and problem-solving abilities. The study concludes that collaborative, reflective, and continuous academic supervision serves as an effective strategy for enhancing the quality of Problem-Based Learning and improving the overall quality of vocational education in vocational high schools.